1993
DOI: 10.1128/jb.175.19.6220-6228.1993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a STreptococcus mutans mutant altered in environmental stress responses

Abstract: A mutant defective in acidurcity, GS5Tn1, was constructed following mutagenesis of Streptococcus mutans GS5 with the conjugative transposon Tn916. The mutant grew poorly at acidic pH levels and was sensitive to high osmolarity and elevated temperatures. These properties resulted from a single insertion of Tn916 into the GS5 chromosome, and the DNA fragment harboring the transposon was isolated in the cosmid vector, charomid 9-20. Spontaneous excision of Tn916 from the cosmid revealed that Tn916 inserted into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 35 publications
1
95
0
Order By: Relevance
“…Using Tn916 mutagenesis, Yamashita et al (1993) identified an acid-sensitive mutant of S . mutans GS.5 deficient in diacylglyerol kinase, an enzyme involved in phospholipid metabolism and, therefore, in maintenance of membrane architecture and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Using Tn916 mutagenesis, Yamashita et al (1993) identified an acid-sensitive mutant of S . mutans GS.5 deficient in diacylglyerol kinase, an enzyme involved in phospholipid metabolism and, therefore, in maintenance of membrane architecture and composition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a dgkA-null mutant of the oral pathogen S. mutans was more susceptible toward bacitracin than the parental strain, 65 suggesting that C 55 -OH phosphorylation constitutes a bypass of the biosynthetic or recycling pathway when the latter is inhibited. For less evident reasons, the latter mutant was also affected for growth at low pH, 122 the biosynthesis of certain lantibiotics, 18 the formation of biofilms, 124 as well as for virulence. 97 Likewise, DgkA from B. subtilis was shown to be required for sporulation by a mechanism that is yet to be clearly established.…”
Section: Formation and Role Of C 55 -P Derivativesmentioning
confidence: 99%
“…Insertion of transposon Tn916 within the codon of the tenth amino acid from the C terminus of the Dgk homologue causes defective growth of the resulting mutant GS5Tn1 at low pH (Yamashita et al, 1993). In addition, this mutant is sensitive to high osmolarity and elevated temperature (Yamashita et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Insertion of transposon Tn916 within the codon of the tenth amino acid from the C terminus of the Dgk homologue causes defective growth of the resulting mutant GS5Tn1 at low pH (Yamashita et al, 1993). In addition, this mutant is sensitive to high osmolarity and elevated temperature (Yamashita et al, 1993). Chen et al (1998) reported that the S. mutans mutant T8-1 with a similar deletion of the Dgk homologue was defective in lantibiotic mutacin II production, which is related to an environmental stress response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation